2004
DOI: 10.3354/meps282115
|View full text |Cite
|
Sign up to set email alerts
|

Variation in blade morphology of the kelp Eisenia arborea: incipient speciation due to local water motion?

Abstract: The southern sea palm kelp Eisenia arborea produces wide, bullate (bumpy) blades in low-flow areas, whereas in adjacent high-flow areas blades are flat and narrow. Here we determine if morphological differences in these 2 closely associated populations are correlated with physical factors in the environment, and whether this response is a genetically fixed or plastic trait. Both phenotypes were subjected to morphometric analysis, field and laboratory transplant experiments, and genetic analysis (M13 DNA finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 64 publications
3
44
1
2
Order By: Relevance
“…Morphology is affected by wave exposure in many kelp species (e.g. Kawamata 2001, Duggins et al 2003, Roberson & Coyer 2004, Wernberg & Thomsen 2005. Adaptations typically include a proportionally larger holdfast and a thicker and sometimes shorter stipe, which reduces the chance of dislodgement, and smaller, slender and more streamlined blades that reduce the area exposed to the forces of moving water (Gaylord et al 1994, Denny & Gaylord 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Morphology is affected by wave exposure in many kelp species (e.g. Kawamata 2001, Duggins et al 2003, Roberson & Coyer 2004, Wernberg & Thomsen 2005. Adaptations typically include a proportionally larger holdfast and a thicker and sometimes shorter stipe, which reduces the chance of dislodgement, and smaller, slender and more streamlined blades that reduce the area exposed to the forces of moving water (Gaylord et al 1994, Denny & Gaylord 2002.…”
Section: Discussionmentioning
confidence: 99%
“…wave action, Roberson and Coyer 2004;Henkel et al 2007, or temperature, Bolton andAnderson 1987). In recent studies incorporating molecular evidence, a pattern is emerging of molecular variation along environmental gradients which correlates with a level of morphological variation which in the past may have been used to describe diVerent species.…”
Section: Towards a Species Concept For Kelpsmentioning
confidence: 99%
“…To my knowledge, there has been no deWnitive molecular taxonomic study on the possible conspeciWcity of these two taxa, although Baartsch et al (2008) cite the published abstract of Cho et al (2006) and are of the opinion that "there is much evidence … that S. longicruris is conspeciWc with S. latissima. There needs to be a consensus on how to deal with "incipient speciation" within genera: that is the existence of morphological forms with relatively slight diVerences within species, which have diVerent ecologies, and can be separated molecularly (Yotsukura et al 1999;Miller et al 2000;Erting et al 2004;Roberson and Coyer 2004;Lane et al 2007;Uwai et al 2007). As Lindstrom (2001) states: "more work is required to understand vicariance in seaweeds, especially in deciphering when a speciation event has occurred".…”
Section: Towards a Species Concept For Kelpsmentioning
confidence: 99%
“…In laboratory experiments it has been shown that those morphological differences are related to associated nutrient uptake (Kraemer and Chapman 1991b). This relationship between water motion and morphology has been shown for Eisenia arborea subtidal populations by Roberson and Coyer (2004), who also point out that this variability also has a genetic background, even at very short spatial scales. In a previous study on intertidal populations of the same species, but not related to wave exposure, Parada et al (2009) observed positive morphological correlations between maximum stipe length and stipe width.…”
Section: Introductionmentioning
confidence: 62%
“…This phenomenon might be related to a morphological adaptation, with longer stipes and more robust ones in exposed areas. Roberson and Coyer (2004) also found morphological variations in subtidal populations, but they suggested that genetic variability was also present in the morphotypes. Tellier et al (2009) using a combination of four genetic makers, located in the three genomic compartments (chloroplast, mitochondria, and nucleus), showed the presence of two highly divergent lineages in Lessonia nigrescens, a South Pacific intertidal kelp, suggesting even the presence of cryptic species (similar morphology and thus considered as only one taxonomic species).…”
Section: Methodsmentioning
confidence: 99%